Fungal Polysaccharides: Biological Activity Beyond the Usual Structural Properties - Rodrigues, Marcio; Nimrichter, Leonardo; Cordero, Radames; Casadevall, Arturo (Frontiers in Microbiology, 2011)
Abstract Studies on structure and function of polysaccharides in biological systems classically involve sequence and compositional analyses, anomeric configuration, type of glycosidic linkage, and presence of substituents. Recent studies, however, indicates that other structural parameters, so far little explored, can directly influence the biological activity of microbial polysaccharides. Among these parameters, we highlight the molecular dimensions of C. neoformans polysaccharides, which appear to be inversely correlated with their immunobiological activity. These recent observations raise new concepts about the structure and function of polysaccharides, which stimulates the design of new experimental approaches and suggests previously unknown applications.